Intelligent governance for the 21st century a middle way between West and East - Berggruen, Nicolas 1961-; Gardels, Nathan (Polity, 2013)
For decades, liberal democracy has been extolled as the best system of governance to have emerged out of the long experience of history. Today, such a confident assertion is far from self-evident. Democracy, in crisis across the West, must prove itself. This highly timely volume is both a conceptual and practical guide of impressive scope to the challenges of good governance as the world continues to undergo profound transformation in the coming decades.